(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This research aimed to measure the cognitive failures of the research sample, and the research sample was (270) students from the Mathematics Department, College of Basic Education, and the research community was (1438) male and female students for the academic year 2021-2022. The cognitive failure scale was used. And came up with the following recommendations - Applying the cognitive failure scale to students in primary and secondary schools. - Reducing the reluctance of mathematics departments in the first place ,To increase the efficiency of future teachers. - Urging university professors to address cognitive failures while teaching mathematics department students The results of the current search were: The presence of cognitive failures among students of the mathematics department in the faculties of basic education